Cross-calibration of multi-frequency bioelectrical impedance analysis with eight-point tactile electrodes and dual-energy X-ray absorptiometry for assessment of body composition in healthy children aged 6-18 years - Lim, Jung S.; Hwang, Jin S.; Lee, Jun A.; Kim, Dong H.; Park, Kyung D.; Jeong, Jin S.; Cheon, Gi J. (Pediatrics international, 2009)
Background:  In diagnosis and treatment of obesity, body composition analysis including percent body fat (%BF) is useful in the clinical setting. Because bioelectrical impedance analysis (BIA) could be used quickly, easily and was non‐invasive in clinical setting, the purpose of the present study was to evaluate the usefulness of multi‐frequency BIA with eight‐point tactile electrodes (MF‐BIA8; InBody 720, Biospace) compared with dual‐energy X‐ray absorptiometry (DXA) in healthy children and adolescents. Methods:  A total of 166 children and adolescents under 18 (male, n = 86; female, n = 80) were recruited. Height, weight, body mass index (BMI) and Tanner stage were measured for each subject. The body composition such as fat‐free mass (FFM), fat mass (FM), and %BF was measured on BIA and DXA and compared. Results:  On linear regression analysis, DXA FFM = 1.006(BIA FFM) + 0.554, R2 = 0.99 and the standard error of the estimate (SEE) was 1.16 kg; DXA FM = 0.971(BIA FM) – 0.596, R2 = 0.93; SEE, 1.34 kg; and DXA %BF = 0.940(BIA %BF) – 1.026, R2 = 0.858; SEE, 3.03%. Limit of agreement in FFM, FM, and %BF was 0.7 ± 2.3 kg, −0.9 ± 2.9 kg and –2.2 ± 6.1%, respectively. Conclusions:  Although the %BF was not interchangeable with DXA, MF‐BIA8 (InBody 720; Biospace) could be used to measure body composition of children and adolescents in the clinical field because of its high precision.